The green fuse [videorecording] - Abadilla, Domingo C.; Patolot, Mike.; Trofeo, Dick. ([S.l.] The Philippine Futuristics Society, [production company] ; Makati : Felta Book Sales, [distributor], 1990)
Summary: Focuses on forest conservation and environmental protection. Shows some of the forest that are denuded and the factors that causes their destruction such as illegal logging.
VHS.
Credits: Narrator, Bong Lapira.
Keywords: Forest conservation; Agriculture; Environmental science